DINAMIKA IMPLEMENTASI PROSEDUR KEAMANAN PENERBANGAN: STUDI MULTI-PERSPEKTIF DI BANDARA INTERNASIONAL SAM RATULANGI MANADO - Sazli Nur Chalis Djafar; Ogi, Imelda W. J.; Palandeng, Indrie Debbie (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2025)
This study aims to analyze the gap between international and national aviation security regulations and field-level operational practices through a multi-perspective study. Adopting a qualitative approach with a phenomenological design, data were collected through in-depth interviews, participant observation, and document analysis at Sam Ratulangi International Airport, Manado. The findings reveal the existence of "conditional compliance," which is influenced by internal factors such as personnel fatigue and external factors such as throughput pressure. The primary results formulate the "Operational Deviation Cascade Model," which explains the process of procedural inconsistency resulting from the interaction between workload and weak supervision. Furthermore, this research formulates the "Stopping Point Model" as a transition mechanism where service orientation must completely cease to be replaced by absolute security control when anomalies occur. The integration of Service Quality Theory and Operation Management Theory is proposed as a systemic framework to bridge the 20.61% compliance gap identified in the security audit. This study provides a practical contribution to airport management in designing adaptive security policies based on human factor mitigation.